VIRUS INFLUENZA NOVEL H1N1 BABI DI INDONESIA - Dharmayanti, NLP Indi; Ratnawati, Atik; Hewajuli, Dyah Ayu (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTNovel H1N1 influenza virus in Swine in Indonesia. Novel H1N1 influenza virus occurred sinceApril 2009 has caused mortality in human population. In Indonesia, this situation requireintensive surveillance to prevent reassortant probability between the H5N1 virus and novelH1N1 virus. This study conduct preliminary surveillance of novel H1N1 virus circulation byusing Real Time-Reverse Transcriptase Polymerase Chain Reaction (qRT-PCR), that validatedby CDC to detect novel H1N1 virus. Result of this study revealed that the influenza novelH1N1 virus was detected in swine/pigs in Indonesia especially in Bulan island and two individualsample from Kapok slaughter house in Jakarta. These findings showed that in Indonesia thenovel H1N1 virus is not only found in human but also has circulated in swine in Indonesia.Key words: pig/swine, influenza novel H1N1 virus